Uma abordagem introdutória ao estudo de triângulos com o software GeoGebra - Silva Júnior, Nelson Claudiano da (2014)
A good teacher is always seeking to improve the quality of their teaching , and one of the factors for achieving this goal is the improvement of teaching techniques , coupled with new technologies . Within this universe , are computerized classes , where micro computers as instructional aids are used . Among the several existing educational software in the market, we can highlight in the area of mathematics, some that are of utmost importance for the development of mathematical thinking by the student . Following this reasoning , the author will highlight this work , the advantages of a new way of teaching geometry in a way that only a computerized environment can provide : Dynamic Geometry , characterized by " drawings in motion." Within this context , accounting software working with dynamic geometry , Geogebra will be presented . Through archival research, the author will present definitions of dynamic geometry , mention information on computing in education , define topics of geometry in the eighth grade of elementary school , in particular , any notable points of triangles , conduct a field study with classes at the Colégio Militar de Fortaleza, to check for relevance of this educational program for classes . At the end of the field research , it will be checked if the geometry classes in elementary school can become more exciting and interesting with the use of this software , which can be very useful as an additional tool for improving the teaching- learning process .